2020
DOI: 10.1177/1071100720943843
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Revision Surgery After Failed Kidner Procedure for Painful Accessory Navicular

Abstract: Background: The Kidner procedure is performed to treat painful accessory navicular syndrome, with varying results. Recurrent pain remains a complication, and to date, there is a paucity of literature regarding the causes of recurrent pain and surgical outcomes of revision. Methods: Twenty-one patients who underwent revision surgery for recurrent pain after the Kidner procedure were identified. All patients had their tendon inspected and treated, and all had a medial displacement calcaneal osteotomy. Revision w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…By medially shifting the calcaneal tubercle, MDCO can not only improve the deformity, but also effectively relieve the tension around the PTT attachment. [15,16] Numerous studies have reported significant pain relief, corrected alignment, and improved function following MDCO. [17][18][19] As a result, MDCO is generally accepted for mild flat foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…By medially shifting the calcaneal tubercle, MDCO can not only improve the deformity, but also effectively relieve the tension around the PTT attachment. [15,16] Numerous studies have reported significant pain relief, corrected alignment, and improved function following MDCO. [17][18][19] As a result, MDCO is generally accepted for mild flat foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Kidner's assumption is that the presence of AN modifies the position and biomechanics of the insertion of the posterior tibialis tendon. This causes weakness in the longitudinal arch of the foot and flatfoot [8]. The method of final elements (FE analysis) is included in the contemporary methods of numerical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that accessory navicular is associated with flatfoot, which induces or worsens the accessory navicular-related symptoms. Simply treating painful accessory navicular could not correct the flatfoot deformity satisfactorily [ 1 , 5 7 ]. The progression of flatfoot deformity induces the progressive collapse of the arch, leading to rigid flatfoot and arthritis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidner procedure reconstructs can alleviate or eliminate the pain in navicular tuberosity. However, whether could persistently correct the collapse of the arch is yet to be elucidated [ 7 ]. Subtalar arthroereisis is an effective method for the treatment of flexible flatfoot in children [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%